2016
DOI: 10.2507/ijsimm15(2)6.334
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Novel Nozzle Used for Pulse Jet Filtration Using CFD Simulation Method

Abstract: The nozzle is one of the most important components of pulse jet systems. The optimization of a pulse jet system and its optimal operation condition are barely known because of the complicated turbulent mixing, compressibility effects, and even flow unsteadiness, which are generated in the nozzle system. In this study, a three-dimensional numerical model of a pulse jet system was established to analyse its operation characteristics by using computational fluid dynamics (CFD). The CFD simulation results were val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In Dai’s analysis, 20 the changing trend of oil volume fraction and pressure on a certain plane were investigated by the developed CFD model of a spur gear pair, and the oil nozzle location parameters were also optimized. Li et al 21 built a three-dimensional numerical model of a pulsed jet system to investigate the operation characteristics by the CFD method, the numerical results are verified by the experimental results. Wang et al 22 were paying attention to the deviation of the jet direction of the aero-engine lubrication system in virtue of the CFD method, it was found that the nozzle injection direction deviation was mainly caused by the radial velocity component at the injector inlet.…”
Section: Introductionmentioning
confidence: 97%
“…In Dai’s analysis, 20 the changing trend of oil volume fraction and pressure on a certain plane were investigated by the developed CFD model of a spur gear pair, and the oil nozzle location parameters were also optimized. Li et al 21 built a three-dimensional numerical model of a pulsed jet system to investigate the operation characteristics by the CFD method, the numerical results are verified by the experimental results. Wang et al 22 were paying attention to the deviation of the jet direction of the aero-engine lubrication system in virtue of the CFD method, it was found that the nozzle injection direction deviation was mainly caused by the radial velocity component at the injector inlet.…”
Section: Introductionmentioning
confidence: 97%
“…These are various pneumatic, electrical, and hydraulic manipulators for sorting larger objects. Ejecting with compressed air and pneumatic nozzles for smaller objects is also widely used [30][31][32]. There are also advanced algorithms for tracking and simulating single particle excretion.…”
Section: Introductionmentioning
confidence: 99%
“…The flow dynamics of a novel nozzle were analysed to predict the effects of nozzle shape and dimensions on the operational performance in terms of pressure and velocity distribution [12]. Li et al and Wang et al conducted a series of studies on oil jet lubrication performance based on a CFD numerical simulation, which showed that for into-mesh jet lubrication, a small angle deviation to the pinion will result in a better lubrication effect [13][14][15].…”
Section: Introductionmentioning
confidence: 99%